Counselling Services and Self-Esteem among Children with Physical Disabilities in Public Primary Schools in Anambra State - Chinwe Augustina Enwere; Queen Nneka Onunkwo (EduGrows: Education and Learning Review, 2026)
Children with physical disabilities in public primary schools often face unique psychological challenges, particularly regarding the development of their self-esteem. The study investigated the effects of counseling services on the growth of self-esteem in children with physical disabilities within public primary schools in Anambra State. Utilizing a descriptive survey research design, data were collected from a purposive sample of 100 respondents using a structured 4-point Likert questionnaire. Data analysis was conducted via SPSS, employing Pearson correlation, simple regression, and hierarchical multiple regression. A significant positive relationship was found between counseling services and self-esteem development, where r equals 0.506 and p equals 0.000. Regression analysis confirmed counseling services significantly predicted self-esteem, accounting for 25.6 percent of its development, with R squared at 0.256, F at 33.740, and p at 0.000. Demographic factors did not significantly moderate this relationship, as gender showed p at 0.359, age showed p at 0.549, and class level showed p at 0.675. Counseling services are crucial for increasing self-esteem among physically disabled children, independent of demographic factors. Consequently, schools should intensify counseling programs to enhance the mental health of these learners.